Regulation and Possible Functions of Kisspeptin in the Medial Amygdala - Stephens, Shannon B. Z.; Kauffman, Alexander S. (Frontiers in Endocrinology, 2017)
Kisspeptin, encoded by the Kiss1 gene, is required for reproduction. Humans and mice lacking kisspeptin or its receptor, Kiss1r, have impairments in reproductive physiology and fertility. In addition to being located in the hypothalamus in the anteroventral periventricular and arcuate nuclei, kisspeptin neurons are also present in several extra-hypothalamic regions, such as the medial amygdala (MeA). However, while there has been a significant focus on the reproductive roles of hypothalamic kisspeptin neurons, the regulation and function(s) of MeA and other extra-hypothalamic kisspeptin neurons have received far less attention. This review summarizes what is currently known about the regulation, development, neural projections, and potential functions of MeA kisspeptin neurons, as well as kisspeptin signaling directly within the MeA, with emphasis on data gathered from rodent models. Recent data is summarized and compared between rodent species and also between males and females. In addition, critical gaps in knowledge and important future directions are discussed.